MANAJEMEN PENDIDIKAN NILAI-NILAI MORAL PADA ANAK (Studi Kasus Di SD Muhammadiyah 1 Alternatif Kota Magelang) (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The research aims to know: 1) the model of implementating educational management on pupil’s moral values, 2) educational management in moral values for the children, 3) the cooperation with other institutions, and 4) the barriers of moral values.This research used qualitative research by study case design. This research is done at the beginning of  March until May 2014. Data was collected by obeservation,  interview, and analyzing document. Analysis  through the phase of data reducing,  data displaying up to the making conclusion or verification.The result are: first, the implementation of education management models of moral values carried through habituation learning in the classroom by providing hands-on experience to students. Among say hello, shake hands, and pray together. Second, management education moral values are integrated in the school's annual program that is boarding lightning and Eid Sacrifice. Third, cooperation is performed between the citizens of the school, college, institute of psychology and surrounding communities. Fourth, the obstacle is the lack of an exemplary figure of parents guardians of students in the school. External barriers are less supportive family environment on children's positive habituation.